Sustainable Hospitality: Reinventing Business Management Practices and the Overall Customer Experience - Fadlallah, Raouf; Marneros, Stelios; Papageorgiou, George (My University, 2025)
The hospitality industry is undergoing a transformative shift toward sustainability, driven by the urgent need to reduce environmental impact and adopt circular economy principles. This chapter explores how innovation and circular business models address environmental, economic, and social challenges in the sector. It highlights the industry's intensive use of natural resources and significant waste generation, noting a persistent gap between sustainability goals and actual practice. Key barriers include striking a balance between eco-friendly operations and service quality, as well as prioritizing long-term sustainability over short-term profits. The chapter calls for systemic change, positioning the hospitality industry as a model for sustainable development. By embracing circular innovation and aligning with the Sustainable Development Goals (SDGs), the sector can transition toward business models that conserve resources, strengthen ecosystem resilience, and generate lasting value.